THE USE OF STYLISTIC TOOLS IN THE SPEECH OF POLITICIANS IN ENGLISH AS A MEANS OF INCREASING SPEECH EFFECTIVENESS (Scientific journal of the Fergana State University, 2025)
This article explores the importance of stylistic tools in English-language political discourse in increasing the effectiveness of speech. The study analyzes how policymakers use stylistic tools such as metaphor, anaphora, parallelism, rhetorical question, and hyperbola. These tools are shown to serve not only to make speech memorable, but also to influence the emotions of the audience and direct them to certain points of view. The article highlights the role of these tools in inspiring, uniting and motivating the masses, giving examples from the speeches of famous politicians.